Bioinspired Design of Ultrathin 2D Bimetallic Metal–Organic‐Framework Nanosheets Used as Biomimetic Enzymes. Issue 21 (23rd March 2016) - Wang, Yixian; Zhao, Meiting; Ping, Jianfeng; Chen, Bo; Cao, Xiehong; Huang, Ying; Tan, Chaoliang; Ma, Qinglang; Wu, Shixin; Yu, Yifu; Lu, Qipeng; Chen, Junze; et al.
Abstract : With the bioinspired design of organic ligands and metallic nodes, novel ultrathin 2D bimetallic metal–organic‐framework nanosheets are successfully synthesized, which can serve as advanced 2D biomimetic nanomaterials to mimic heme proteins.